On the economic impact of FDI and trade liberalization in the Asia-Pacific region: A structural quantitative analysis - Mario Larch; Yoto V. Yotov (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2017)
We employ the structural model of trade and investment from Anderson, Larch and Yotov (2017) in order to quantify the impact of Foreign Direct Investment (FDI) and trade liberalization on exports and real GDP per capita in the Asia-Pacific region. Using a dataset of 89 countries for 2011, which covers more than 97 percent of the trade and investment activity in the ESCAP member countries form the Asia-Pacific region, we find that FDI has had a strong but heterogeneous impact on the economic performance of the countries in this region. On average, our estimates reveal that FDI is responsible for 7% of exports, for 3% of physical capital accumulation, and for 7% of real GDP per capita in the Asia-Pacific region. We also find that a uniform 10% decrease of bilateral trade costs for all ESCAP members in our sample would have led to strong and positive, but quite heterogeneous, impact on exports and real GDP per capita in the Asia-Pacific region.
Keywords: F21; F13; 330; FDI; trade liberalization; international trade